Prediction of Graft Survival Post-liver Transplantation by L-GrAFT Risk Score Model, EASE Score, MEAF Scoring, and EAD - Chen, Shirui; Wang, Tielong; Luo, Tao; He, Shujiao; Huang, Changjun; Jia, Zehua; Zhan, Liqiang; Wang, Dongping; Zhu, Xiaofeng; Guo, Zhiyong; He, Xiaoshun (Frontiers in Surgery, 2021)
Background: Early allograft dysfunction (EAD) is correlated with poor patient or graft survival in liver transplantation. However, the power of distinct definitions of EAD in prediction of graft survival is unclear. Methods: This retrospective, single-center study reviewed data of 677 recipients undergoing orthotopic liver transplant between July 2015 and June 2020. EAD definitions of Liver Graft Assessment Following Transplantation (L-GrAFT) risk score model, Early Allograft Failure Simplified Estimation score (EASE), Model for Early Allograft Function (MEAF) Scoring and Olthoff criteria were compared. Risk factors for L-GrAFT7 high risk group were evaluated with univariate and multivariable logistic regression analysis. Results: L-GrAFT7 had a satisfied C-statistic of 0.87 in predicting 3-month graft survival which significantly outperformed, MEAF (C-statistic =0.78, P=0.01) and EAD (C-statistic =0.76, P <0.001), respectively. L-GrAFT10, EASE was similar to L-GrAFT7, and they had no statistical significance in predicting survival. Laboratory Model for End-Stage Liver Disease score and cold ischemia time are risk factors of L-GrAFT7 high-risk group. Conclusion: L-GrAFT7 risk score is capable for better predicting 3-month graft survival than the MEAF and EAD in a Chinese cohort, which might standardize assessment of early graft function and serve as a surrogate endpoint in clinical trial.